A comparative assessment of net metering and feed in tariff schemes for residential PV systems - Poullikkas, Andreas (2013)
In this work, a comparative assessment of net metering vs. feed-in-tariff (FiT) supporting schemes for residential PV systems is carried out. A formulation for the computation of net metering supporting scheme parameters, in half hour intervals, is developed and typical household integrated with a rooftop PV system is investigated. The effect of the size of PV system with respect to the net metering supporting scheme is examined by varying the PV capacity and the effect of the electricity retail cost rate is investigated by varying the electricity retail cost rate. The comparative results indicate that net metering supporting scheme performs better than a FiT supporting scheme when the household electricity bill is taken into account. From the analysis it is clear that under certain conditions net metering supporting scheme becomes profitable.